Endocannabinoid System and Nitric Oxide are Involved in the Deleterious Effects of Lipopolysaccharide on Murine Decidua - Vercelli, Claudia Alejandra (2009)
Endocannabinoids are an important family of lipid-signaling molecules that are widely distributed in mammalian tissues and anandamide (AEA) was the first member identified. The uterus contains the highest concentrations of AEA yet discovered in mammalian tissues and this suggests that it might play a role in reproduction. Previous results from our laboratory have shown that AEA modulated NO synthesis in rat placenta. The production of small amounts of nitric oxide regulates various physiological reproductive processes such as implantation, decidualization and myometrial relaxation. But in an inflammatory setting such as sepsis, NO is produced in big amounts and has toxic effects as it is a free radical. The results presented in this study indicate that LPS-induced NO synthesis and tissue damage were mediated by AEA. Decidual LPS-induced NO production was abrogated either by co-incubation with CB1 (AM251) or CB2 (SR144528) antagonists which suggests that both receptors could be mediating this effect. On the other hand, LPS-induced tissue damage and this deleterious effect was partially abrogated by incubating tissue explants with LPS plus CB1 receptor antagonist. Our findings suggest that AEA, probably by increasing NO synthesis, participates in the deleterious effect of LPS in implantation sites. These effects could be involved in pathological reproductive events such as septic abortion.